2008
DOI: 10.1158/0008-5472.can-08-0202
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Regulates Macrophage-Mediated Angiogenesis in a Mouse Model of Colon Cancer Allografts

Abstract: Serotonin, a neurotransmitter with numerous functions in the central nervous system (CNS), is emerging as an important signaling molecule in biological processes outside of the CNS. Recent advances have implicated serotonin as a regulator of inflammation, proliferation, regeneration, and repair.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 26 publications
6
95
1
4
Order By: Relevance
“…A link between 5HT and macrophages in cancer progression has been already established, as 5HT enhances angiogenesis in murine colon cancer allografts via the 5HT-dependent reduction of MMP12 expression by tumor-infiltrating macrophages (26). Our results on the phenotypic changes induced by 5HT and BW723C86 on human macrophages are compatible with these findings because: 1) both stimuli inhibit MMP12 mRNA expression (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A link between 5HT and macrophages in cancer progression has been already established, as 5HT enhances angiogenesis in murine colon cancer allografts via the 5HT-dependent reduction of MMP12 expression by tumor-infiltrating macrophages (26). Our results on the phenotypic changes induced by 5HT and BW723C86 on human macrophages are compatible with these findings because: 1) both stimuli inhibit MMP12 mRNA expression (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 89%
“…4). These results are in agreement with the reported ability of 5HT to reduce the expression of MMP12 in murine macrophages (26), and they demonstrate that both 5HT and the 5HT 2B agonist BW723C86 influence the phenotypic macrophage polarization.…”
Section: Ht and 5ht 2b Receptor Engagement Trigger Intracellular Sigsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to enhancing our understanding of the role of 5-HT on immune cell signaling and pathogenesis of colitis, this study identified a potential therapeutic strategy for intestinal inflammatory disorders, including IBD, by targeting 5-HT signaling. Intestinal 5-HT has not only been shown to be important in modulating gut inflammation, but recent studies have also shown that 5-HT deficiency causes slower growth of colon cancer allografts in vivo (73), and reduction in gut-derived 5-HT synthesis decreases development of osteoporosis by promoting bone formation (74). Thus, in a wider perspective, these data have implications not only in developing strategies in ameliorating GI inflammatory disorders such as IBD, but also in non-GI inflammatory conditions that are associated with alterations in 5-HT signaling in the gut.…”
Section: Cd11cmentioning
confidence: 99%
“…Serotonin does not enhance tumor cell proliferation, but acts as a regulator of angiogenesis by reducing the expression of matrix metalloproteinase 12 (MMP-12) in tumor-infiltrating macrophages, entailing lower levels of angiostatin-an endogenous inhibitor of angiogenesis. Accordingly, serotonin deficiency causes slower growth of colon tumors by reducing vascularity, thus increasing hypoxia and spontaneous necrosis [35]. In alveolar macrophages serotonin significantly inhibits the production of tumor necrosis factor (TNF) and interleukin (IL)-12, whereas IL-10, NO and PGE(2) production are increased.…”
Section: Serotoninmentioning
confidence: 99%